2022
DOI: 10.1002/cbin.11866
|View full text |Cite
|
Sign up to set email alerts
|

An oleanolic acid derivative, K73‐03, inhibits pancreatic cancer cells proliferation in vitro and in vivo via blocking EGFR/Akt pathway

Abstract: Oleanolic acid (OA) and its derivatives show potent anticancer function. Pancreatic cancer (PC) is the fourth core motive of cancer-related deaths worldwide. Epidermal growth factor receptor (EGFR) has been implicated in PC and has been validated as a therapeutic target. Our study demonstrated that K73-03, an OA derivative, was identified as a potent inhibitor of EGFR by using reverse pharmacophore screening and molecular dynamics simulation assays. Moreover, Western blot analysis showed that K73-03 markedly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Similar suggestions were raised by Xie et al, who showed that ERα was the target for OA, and OA upregulated miR-503 expression through ERα in RAW264.7 cells (macrophage-like cells) [ 49 ]. Moreover, the OA analog, K73-03, was used as an effective anticancer agent that acted via targeting EGFR in pancreatic ASPC-1 cancer cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar suggestions were raised by Xie et al, who showed that ERα was the target for OA, and OA upregulated miR-503 expression through ERα in RAW264.7 cells (macrophage-like cells) [ 49 ]. Moreover, the OA analog, K73-03, was used as an effective anticancer agent that acted via targeting EGFR in pancreatic ASPC-1 cancer cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The titled compound caused G2/M-phase arrest and suppressed ASPC-1 cells migration. Immunoblot assay exposed that K73-03 repressed the phosphorylation EGFR and Akt leading to a remarkable in vitro and in vivo anti-PC effect [72].…”
Section: Oleanane Type Pts In Pancreatic Cancermentioning
confidence: 99%
“…Nuclear factor-κB (NF-κB) signaling pathway Anti-inflammatory, antitumor [65][66][67][68] Nod-like receptor pyrin domain containing 3 (NLRP3) signaling pathway Anti-inflammatory, neuroprotection [69][70][71] Extracellular-signal-regulated kinase (ERK) signaling pathway Liver protection, antitumor [72,73] Protein kinase B/Akt signaling pathway Antitumor, liver protection [72,74,75] Jun N-terminal kinases (JNK) signaling pathway Antitumor [1,75] Orphan receptor γ t signaling pathway Anti-inflammatory, anti-asthma [76] Mitogen-activated protein kinases (MAPK) signaling pathway Anti-inflammatory [77,78] MiR-122/cyclin G1/myocyte enhancer factor 2D (miR-122/CCNG1/MEF2D) signaling pathway Antitumor [79] Cyclic adenosine 3 ,5 -monophosphate/protein kinase A (cAMP/PKA) signaling pathway Lowers blood sugar and blood lipids, protects pancreatic islets [80] Phosphatidylinositol 3-kinase/AKT/mammalian target of rapamycin (PI3K/AKT/mTOR) signaling pathway Anti-osteoarthritis [81] Endothelial nitric oxide synthase/Akt/nitric oxide (eNOS/Akt/NO) signaling pathway Ameliorates high glucose-induced endothelial dysfunction [82] Signal transducer and activator of transcription 3 (STAT3) and sonic hedgehog (SHH) signaling pathway Inhibits colorectal cancer [83] Mitogen-activated protein kinase kinase (MEK)/ERK/JNK signaling pathway Anticancer [84] Hippo-Yes-associated protein (Hippo-Yap) signaling pathway Anti-stomach cancer [85] Epidermal growth factor (EGFR)/AKT signaling pathway Anti-pancreatic cancer [86] Nuclear factor erythroid 2-related factor 2 (Nrf-2) signaling pathway Liver protection, antidiabetic, anti-inflammatory, maintenance of redox and protein homeostasis [87][88][89] 3.1. Anti-Inflammatory Effect of OA…”
Section: Signaling Pathway Biological Activity Referencementioning
confidence: 99%